Characteristics Of The Ghazal Genre In Chustiy’s Lyrics - Otakhanova Mahmuda Mamadaliyevna (Zien Journals, 2024)
This article studies the classification of ghazals and their specific features in the lyrics of the poet Chustiy (Nabikhan Khojayev). Also, the high artistic skill of the poet in lyrics is revealed. For the first time, the ghazals included in the author's books "Hayatnoma" and "Sadoqat Gullari" were formally and poetically analyzed, and the ideas were proved with concrete examples. The analysis was carried out, using comparative-historical, hermeneutic and biographical methods. When writing ghazals in lyric poetry, Chustiy always followed the traditions of his great predecessors. In particular, a magician of words - Alisher Navoi's work became a source of inspiration for the poet. A number of such peculiarities are highlighted in the article
Keywords: ghazal; pseudonym; simple ghazals; ghazal muvashshah